Method and system for representing densification of amorphous material under mechanical deformation
By applying mechanical loads to amorphous materials and combining transmission electron microscopy and electron diffraction pattern analysis, the problem of accurate characterization of amorphous material densification was solved, achieving high-resolution densification detection and quantification, and promoting reliable prediction and optimization of material properties.
Patent Information
- Application Number
- CN202510918196.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies cannot accurately quantify the densification phenomenon of amorphous materials during mechanical deformation, leading to errors in material performance evaluation. Furthermore, they cannot separate and quantify the densification contribution under controlled deformation paths.
A mechanical deformation method was used to apply a load to the amorphous material, and cross-sectional samples were prepared by focusing ion beam technology. The densified regions were then accurately identified and quantified by transmission electron microscopy and electron diffraction pattern analysis.
It achieves high-resolution detection and quantitative analysis of densification of amorphous materials under controlled deformation paths, provides accurate characterization of the deformation mechanism of amorphous materials, and supports reliable prediction and optimization of material properties.
Smart Images

Figure CN121007913A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of materials science and solid mechanics, and in particular to a method and system for characterizing the densification of amorphous materials under mechanical deformation. Background Technology
[0002] Amorphous materials, such as fused silica, bulk metallic glasses, chalcogenide glasses, and amorphous thermoplastics, are characterized by a lack of long-range translational order, resulting in a significantly different response to mechanical deformation compared to crystalline materials. Due to the lack of periodic atomic arrangement, traditional dislocation-mediated plasticity cannot be activated in amorphous materials, leading to alternative deformation mechanisms such as shear banding, cooperative atomic rearrangement, and more pronounced localized densification.
[0003] Densification in amorphous solids is characterized by an irreversible reduction in free volume and an increase in atomic packing density, typically occurring under hydrostatic pressure or complex stress conditions. This volume compression does not occur through dislocation nucleation and motion, but rather through atomic-scale reorganization and topological rearrangement. For example, in materials such as fused silica, densification plays a dominant role throughout the plastic deformation process, especially under the high contact pressures generated by nanoindentation or scratch testing. Therefore, accurately quantifying densification is crucial for elucidating the deformation physicomechanical mechanisms of amorphous material systems.
[0004] While nanoindentation is widely used to assess hardness, elastic modulus, and other mechanical parameters, the technique itself can obscure the different contributions of plastic response, particularly shear flow and densification. Most conventional interpretations rely on simplified constitutive models that assume homogeneous material behavior and often neglect the unique volumetric composition associated with densification. Consequently, the distinctive mechanical characteristics of densification are frequently masked or misattributed, leading to errors in material property assessments.
[0005] Several methods have been proposed for indirectly inferring densification, including load-displacement curve analysis, energy dissipation models, and spatial stiffness or modulus mapping. However, these methods lack spatial resolution, mechanical specificity, or sensitivity, and cannot clearly distinguish between shear-driven and volume-driven deformations. Furthermore, they fail to capture the anisotropy and heterogeneity of subsurface structural evolution accompanied by indentations or scratches.
[0006] Therefore, a significant technological gap exists in the accurate characterization of densification in amorphous materials. Developing a robust, multi-scale approach capable of separating and quantifying densification contributions under controlled deformation paths is crucial. Such a framework would not only provide fundamental insights into the mechanical behavior of disordered materials but also facilitate the design and optimization of amorphous materials, enabling them to play a role in advanced applications requiring reliable prediction of mechanical properties, such as optics, coatings, biomedical devices, and structural components. Summary of the Invention
[0007] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method and system for characterizing the densification of amorphous materials under mechanical deformation, and to provide a robust, multi-scale method that can separate and quantify densification contributions under controlled deformation paths.
[0008] The technical solution of the present invention is as follows:
[0009] A first aspect of the present invention provides a method for characterizing the densification of amorphous materials under mechanical deformation, the method comprising the following steps:
[0010] Applying a mechanical load to an amorphous material induces localized plastic deformation of the amorphous material;
[0011] A cross-sectional sample was prepared by milling the deformation region of the amorphous material using focused ion beam technology. The microstructural changes of the cross-sectional sample were then obtained by transmission electron microscopy to confirm the densification region of the cross-sectional sample.
[0012] The degree of densification of the cross-sectional sample is detected and quantified by analyzing electron diffraction patterns.
[0013] Optionally, the amorphous material is selected from oxide-based glass, metallic glass, chalcogenide glass, or thermoplastic amorphous polymer.
[0014] Optionally, the step of applying a mechanical load to the amorphous material specifically involves applying a mechanical load to the amorphous material under a controlled environment, wherein the controlled environment includes controlled changes in strain rate and temperature.
[0015] Optionally, the mechanical load may include nanoindentation, variable load nanoscratch testing, or microcompression.
[0016] Optionally, after obtaining the microstructural changes of the cross-sectional sample by transmission electron microscopy, the method further includes the step of separating the compacted region of the cross-sectional sample from the shear-induced banded or flow-localized region by high-resolution transmission electron microscopy.
[0017] Optionally, the step of quantifying the densification degree of the cross-sectional sample specifically involves: establishing a functional correlation between the local displacement of the nanobeam electron diffraction or selected area electron diffraction pattern and the material density of the cross-sectional sample, and verifying it through complementary image contrast analysis, energy-filtered transmission electron microscopy, or electron energy loss spectroscopy.
[0018] Optionally, after detecting and quantifying the densification degree of the cross-sectional sample by analyzing the electron diffraction pattern, the method further includes the step of integrating the densification information obtained in the above steps into a constitutive model to predict the mechanical response and densification behavior of the amorphous material under applied load conditions.
[0019] A second aspect of the present invention provides a system for characterizing the densification of amorphous materials under mechanical deformation, the system comprising:
[0020] Nanoindentation platforms and / or nanoscratching platforms can provide high-resolution mechanical load profiles and enable in-situ load, displacement, and strain rate control.
[0021] A microscopic imaging device is used to prepare cross-sectional samples at specific locations, identify densified regions in the cross-sectional samples, and perform densification analysis.
[0022] The computation module is used to fit physical information such as mechanical load-displacement data, spectral information, and microstructure characterization to the intrinsic model supported by densification through inverse modeling or finite element simulation framework.
[0023] Optionally, the microscopic imaging apparatus includes a focused ion beam milling device and a transmission electron microscope.
[0024] The present invention has the following beneficial effects:
[0025] This invention proposes a method and system for characterizing the densification of amorphous materials under mechanical deformation. The method provided by this invention has the following advantages: by using transmission electron microscopy (TEM) diffraction contrast and nano-electron diffraction displacement analysis, the volume compression can be quantitatively evaluated, and the local structural rearrangement can be directly correlated with the density change of amorphous materials. This allows for the accurate identification, quantification, and spatial visualization of the densification phenomenon of amorphous materials during mechanical deformation. Attached Figure Description
[0026] Figure 1 Nanobeam electron diffraction (NBED) analysis of scratch-fused silica densification at different temperatures in this embodiment of the invention: (a) representative NBED pattern; (b) circumferential average intensity distribution I(q) derived from the diffraction pattern; (c) reduced intensity function φ(q) calculated from I(q); (d) reduced density function (RDF) of the original sample (red) and the densified region (blue); (e) local atomic structure analysis. (f) Left: Cross-sectional bright-field TEM image showing the densification boundary (dashed line) and NBED measurement location (colored arrow) of fused quartz tested at room temperature; Right: Distribution of corresponding density ratios measured at different underground depths, where ρ0 = 2.20 g / cm³. 3 This represents the initial density of undeformed fused quartz. Detailed Implementation
[0027] This invention provides a method and system for characterizing the densification of amorphous materials under mechanical deformation. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0029] Recent advances in experimental techniques such as high-resolution transmission electron microscopy (HR-TEM), Raman spectroscopy, and synchrotron X-ray diffraction, along with computational modeling methods such as molecular dynamics (MD) simulations and finite element analysis (FEA), have demonstrated the potential to reveal structural changes at finer scales. However, a framework with atomic-level resolution and quantitative analytical capabilities that integrates these tools and spatially maps densification under well-defined mechanical boundary conditions has yet to be found.
[0030] Based on this, embodiments of the present invention provide a method for characterizing the densification of amorphous materials under mechanical deformation, the method comprising the following steps:
[0031] Applying a mechanical load to an amorphous material induces localized plastic deformation of the amorphous material;
[0032] A cross-sectional sample was prepared by milling the deformation region of the amorphous material using focused ion beam technology. The microstructural changes of the cross-sectional sample were then obtained by transmission electron microscopy to confirm the densification region of the cross-sectional sample.
[0033] The degree of densification of the cross-sectional sample is detected and quantified by analyzing electron diffraction patterns.
[0034] This invention induces local densification in amorphous materials through mechanical loading and utilizes cross-sectional micro / nano fabrication and electron microscopy to achieve high-resolution detection and quantitative analysis of the densification. This invention addresses the key challenge of accurately quantifying local structural changes (most notably permanent volume compression, i.e., densification) in amorphous materials under various contact-induced mechanical loads.
[0035] This invention is particularly applicable to high-performance applications requiring predictive control of deformation and densification mechanisms in amorphous materials, such as microelectromechanical systems (MEMS), optical and optoelectronic components, biomedical implants, and triboelectrically loaded surfaces. By combining experimental observation with theoretical modeling within a unified material-specific framework, this invention establishes a new paradigm for quantitatively evaluating the structure-property relationships of amorphous materials. Furthermore, it provides a rigorous analytical framework for optimizing the fabrication processes, mechanical reliability, and functional performance of amorphous devices and components operating under complex loading environments.
[0036] In some embodiments, the amorphous material is selected from oxide-based glass, metallic glass, chalcogenide glass, or thermoplastic amorphous polymer.
[0037] Specifically, oxide-based glasses include quartz and borosilicates; metallic glasses include zirconium-based, palladium-based, or copper-based systems; chalcogenide glasses include As2Se3 and GeSbTe alloys; and thermoplastic amorphous polymers include PMMA and polycarbonate.
[0038] In some embodiments, the step of applying a mechanical load to the amorphous material specifically involves applying a mechanical load to the amorphous material under a controlled environment, wherein the controlled environment includes controlled changes in strain rate and temperature, to capture the thermally activated characteristics of the densification mechanism.
[0039] In some embodiments, the mechanical load includes nanoindentation, variable load nanoscratch testing, or microcompression.
[0040] In some embodiments, after obtaining the microstructural changes of the cross-sectional sample by transmission electron microscopy, the method further includes the step of separating the densified region of the cross-sectional sample from the shear-induced banded or flow-localized region by high-resolution transmission electron microscopy.
[0041] By integrating local structural characterization and deformation mapping at nanoscale resolution, we can distinguish between densification and concurrent plastic deformation mechanisms such as shear bands and uniform shear flow.
[0042] In some embodiments, the step of quantifying the densification degree of the cross-sectional sample specifically involves: establishing a functional correlation between the local displacement of the nanobeam electron diffraction or selected area electron diffraction pattern and the material density of the cross-sectional sample, and verifying it by complementary image contrast analysis, energy-filtered transmission electron microscopy, or electron energy loss spectroscopy.
[0043] In some embodiments, after detecting and quantifying the densification degree of the cross-sectional sample by analyzing electron diffraction patterns, the method further includes the step of integrating the densification information obtained in the above steps into a constitutive model to predict the mechanical response and densification behavior of the amorphous material under applied load conditions.
[0044] This invention also provides a system for characterizing the densification of amorphous materials under mechanical deformation, the system comprising:
[0045] Nanoindentation platforms and / or nanoscratching platforms can provide high-resolution mechanical load profiles and enable in-situ load, displacement, and strain rate control.
[0046] A microscopic imaging device is used to prepare cross-sectional samples at specific locations, identify densified regions in the cross-sectional samples, and perform densification analysis.
[0047] The computation module is used to fit physical information such as mechanical load-displacement data, spectral information, and microstructure characterization to the intrinsic model supported by densification through inverse modeling or finite element simulation framework.
[0048] In some embodiments, the microscopic imaging apparatus includes a focused ion beam milling device and a transmission electron microscope.
[0049] In some implementations, the densification parameters extracted by the above system include, but are not limited to: density change obtained by diffraction-based density calibration; densification initiation pressure corresponding to the critical load at which permanent compaction begins; and geometric parameters of the densified region, such as depth, lateral extension, and aspect ratio, determined by cross-sectional transmission electron microscopy (TEM) imaging and simulation of deformation fields.
[0050] The following detailed description uses specific examples.
[0051] Example
[0052] A method for characterizing the densification of amorphous materials under mechanical deformation includes the following steps:
[0053] Step 1: Controlled mechanical load
[0054] Depth-sensing nanoindentation or gradient nanoscratching tests were performed on fused silica under different loads, loading rates, residence times, and ambient temperatures.
[0055] High stress concentration is generated by using a sharp Berkovich indenter, which promotes densification in local areas.
[0056] Step 2: High-resolution subsurface structure mapping
[0057] Cross-sectional samples were prepared using FIB milling, followed by TEM testing. Density changes derived from contrast variations and diffraction patterns were used to visualize the densified regions. It should be noted that HR-TEM is one type of TEM test. In practice, multiple TEM tests are performed in this step. Whether HR-TEM is needed depends on the required spatial resolution. This embodiment did not perform such a high-resolution test, but HR-TEM would be necessary when extremely high spatial resolution is required.
[0058] Nanoelectron beam diffraction patterns are used to identify subtle rearrangements of atomic packing density to indicate densification.
[0059] Step 3: Quantitative Spectral Analysis of Densification
[0060] Obtain the NBED pattern from the deformed region. Place an electron probe (convergence angle 0.95 mrad, probe size ~1 nm) at the location affected by the scratch. Acquire a diffraction pattern with a resolution of 4096 × 4096 pixels, retaining the central 1024 × 1024 pixels for analysis. Figure 1 (a)
[0061] Process the diffraction data to obtain the intensity distribution I(q). A custom MATLAB algorithm is used to perform azimuth averaging on the diffraction pattern to generate the radial intensity distribution. The scattering vector q = 4πsinθ / λ is calculated, where θ is half the scattering angle and λ is the incident electron wavelength. Lobato's atomic scattering factor parameterization method is applied to ensure accurate background subtraction. The workflow is as follows: Original NBED pattern → Azimuth averaging → Intensity distribution I(q) Figure 1 (b)
[0062] Calculate the reduced density function G(r) based on the intensity distribution. Transform I(q) into the reduced intensity function.
[0063]
[0064] Then apply the Fourier transform.
[0065] G(r) = 4∫0 ∞ φ(q)sin(qr)dq
[0066] Obtain the radial distribution function ( Figure 1 (China ce).
[0067] Densification is quantified through structural analysis. The relation (r0 / r) is used. 3 Determine the density ratio, where r0 is the original bond length and r is the bond length measured from the RDF peak position. For example, at room temperature, the mapped densification distribution with spatial intervals of 50 nm on the cross-section of amorphous fused silica with a scratch ( Figure 1 (fg).
[0068] Step 4: Calculation and Constitutive Model
[0069] Extract key densification parameters: densification threshold stress and densification distribution.
[0070] Based on the densification distribution and material properties measured by other conventional methods, the yield surface of amorphous materials can be determined. The yield criterion can then be determined based on the distribution of the yield surface, leading to the formulation of constitutive laws incorporating the densification effect. Empirical density data and indentation response are integrated into the finite element model. There is no fixed method for calculating the constitutive model; in practical application, the method of this invention is analyzed based on the measured densification distribution, and a constitutive relation model in formulaic form is obtained through various methods such as theoretical formulas, numerical calculations, or neural networks.
[0071] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for characterizing the densification of amorphous materials under mechanical deformation, characterized in that, The method includes the following steps: Applying a mechanical load to an amorphous material induces localized plastic deformation of the amorphous material; A cross-sectional sample was prepared by milling the deformation region of the amorphous material using focused ion beam technology. The microstructural changes of the cross-sectional sample were then obtained by transmission electron microscopy to confirm the densification region of the cross-sectional sample. The degree of densification of the cross-sectional sample is detected and quantified by analyzing electron diffraction patterns.
2. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, The amorphous material is selected from oxide-based glass, metallic glass, chalcogenide glass, or thermoplastic amorphous polymer.
3. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, The step of applying mechanical load to the amorphous material specifically involves applying mechanical load to the amorphous material under a controlled environment, wherein the controlled environment includes controlled changes in strain rate and temperature.
4. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, The mechanical loads include nanoindentation, variable load nanoscratch testing, or microcompression.
5. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, After obtaining the microstructural changes of the cross-sectional sample by transmission electron microscopy, the method further includes the step of separating the compacted region of the cross-sectional sample from the shear-induced banded or flow-localized region by high-resolution transmission electron microscopy.
6. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, The step of quantifying the densification degree of the cross-sectional sample specifically involves: establishing a functional correlation between the local displacement of the nanobeam electron diffraction or selected area electron diffraction pattern and the material density of the cross-sectional sample, and verifying it through complementary image contrast analysis, energy-filtered transmission electron microscopy, or electron energy loss spectroscopy.
7. The method for characterizing the densification of amorphous materials under mechanical deformation according to claim 1, characterized in that, After detecting and quantifying the densification degree of the cross-sectional sample by analyzing the electron diffraction pattern, the method further includes the step of integrating the densification information obtained in the above steps into the constitutive model to predict the mechanical response and densification behavior of the amorphous material under applied load conditions.
8. A system for characterizing the densification of amorphous materials under mechanical deformation, characterized in that, The system includes: Nanoindentation platforms and / or nanoscratching platforms can provide high-resolution mechanical load profiles and enable in-situ load, displacement, and strain rate control. A microscopic imaging device is used to prepare cross-sectional samples at specific locations, identify densified regions in the cross-sectional samples, and perform densification analysis. The computation module is used to fit mechanical load-displacement data, spectral information, and physical information representing microstructures to an intrinsic model supported by densification through inverse modeling or finite element simulation framework.
9. The system for characterizing the densification of amorphous materials under mechanical deformation according to claim 8, characterized in that, The microscopic imaging device includes a focused ion beam milling device and a transmission electron microscope.